A CDA Perspective of Cultural Contents in the English Junior High School Textbooks - Mandarani, Vidya; Purwati, Oikurema; Santoso, Dian Rahma (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
In the aim to engage the volatile future, Kemendikbud considered developing the textbooks with cultural values imbued for the 2013 Curriculum. This study is a content analysis that seeks to examine the cultural elements found in the English textbooks for junior high schoolers, to discover the evidence of global cultural manifestation in the textbooks, as well as to find out the space given to local culture in the textbooks. The data were collected from the latest revision of ‘When English Rings a Bell’ textbook for both 7th & 8th grade, and ‘Think Globally Act Locally’ textbook for 9th grade. The data then analyzed qualitatively. The findings showed that: (1) social group & social identity dictate the cultural dimension, followed by belief & behavior. While another aspect, such as stereotypes & national identity, social interaction, the life-cycle & socialization, national culture heritage, national geography, national history as well as socio-political institution, are not commonly presented. This idea is in line with the curriculum objectives to facilitate the development of students with proper character, behavior and a strong sense of nationality. In terms of proportionality as shown by cultural dimensions, it is inferred that the English textbooks are on their way to perfection; (2) the existence of the target cultures is still dominant, yet the authors had tried to maintain the initial content of the source culture, as well as (3) the students require to realize the importance of learning culture from their English textbooks & develop their cultural competence and a certain degree of respect, as well as tolerance for others.